2005
DOI: 10.1021/es048856h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Addition Order and Contact Time on Thorium(IV) Retention by Hematite in the Presence of Humic Acids

Abstract: The influence of addition order and contact time in the system hematite (α-Fe 2 O 3 ) -humic acid (HA) -thorium (IV) was studied in batch experiments. Thorium (IV) is considered here as a chemical analogue of other actinides (IV). The sorption isotherms were acquired varying pH in the range 2-10, and HA concentration in the range 1-100 mg/L. As already observed by numerous authors, thorium (IV) retention was hindered when HA and hematite were equilibrated beforehand during 24 hours. As it has been observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 66 publications
(142 reference statements)
6
46
0
Order By: Relevance
“…Several studies have attempted to gain a more mechanistic understanding through the use of advanced spectroscopic techniques (Ö sthols, 1995; Ö sthols et al, 1997), or surface complexation modeling (Reiller et al, 2005). However, little attention is usually given to the choice of background electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to gain a more mechanistic understanding through the use of advanced spectroscopic techniques (Ö sthols, 1995; Ö sthols et al, 1997), or surface complexation modeling (Reiller et al, 2005). However, little attention is usually given to the choice of background electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are performed in NO 3 À media (Li and Tao, 2002;Guo et al, 2005;Reiller et al, 2005;Sharma et al, 2006Sharma et al, , 2009Zhang et al, 2006;Sheng et al, 2008;Talip et al, 2009), presumably due to its relevance in chemical-separations processes and its ubiquitous presence in groundwater. Studies in ClO 4 À media are also commonly found (Ö sthols, 1995;Ö sthols et al, 1997;Jakobsson, 1999;Reiller et al, 2005;Rojo et al, 2009). Only one study (Jakobsson, 1999) investigated sorption reactions for multiple background electrolytes, namely NaCl and NaClO 4 (in this case on TiO 2 substrates).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [9] reported that the presence of HSs enhanced Th(IV) sorption on -Al 2 O 3 at lower pH scale while inhibited at intermediate and high pH, which may be attributed to the formation of ternary surface complexes, such as  SO-OC-HA-Th and  SO-OC-FA-Th. Moreover, different addition sequences of HSs would lead to the transform of interaction mechanism between metal ions, HSs and sorbents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decade years, the sorption of Th(IV) on all kinds of minerals as a function of pH, ionic strength, temperature was studied extensively Fan et aL, 2008;Pan et aL, 2011;Hu and Tan, 2012;Zhang et aL, 2015). Many mechanisms have been postulated for Th(IV) and other actinides of sorption, such as surface complexation, chemi-complexation, chemisorption, cation exchange, surface precipitation, colloid formation at surface and diffusion into the particle micropores (Jakobsson,1999;Reiller et aL, 2005;Wang et aL, 2005a;Wang et aL, 2005b;Wang et aL, 2005c) .…”
Section: Introductionmentioning
confidence: 99%